Populist discourse : critical approaches to contemporary politics - Hidalgo Tenorio, Encarnación, 1968-; Benitez-Castro, Miguel-Angel; De Cesare, Francesca (Routledge, 2019)
Populist Discourse brings together experts from both linguistics and political science to analyse the language of populist leaders and the media's representation of populism in different temporal, geographical and ideological contexts, including Nazi Germany, Sweden, the Netherlands, Spain, Italy, Portugal, Austria, Greece, the UK, the US and South America. With17 contributions split into four sections, Populist Discourse covers a variety of approaches such as corpus-based discourse analysis, critical discourse analysis and political perspectives, making it a timely dissection for students and researchers working in linguistics, political science and communication.- Resumé vydavatel